Antifungal effect of cinnamaldehyde, eugenol and carvacrol nanoemulsion against Penicillium digitatum and application in postharvest preservation of citrus fruit. (April 2021) - Yang, Ruopeng; Miao, Jinyu; Shen, Yuting; Cai, Nan; Wan, Chunpeng; Zou, Liqiang; Chen, Chuying; Chen, Jinyin
Abstract: Current study used high pressure microfludizer to encapsulate eugenol (EUG), carvacrol (CAR) and cinnamaldehyde (CA) in oil-in water nanoemulsion. The prime objective of this study was to explore the antifungal effect of these prepared nanoemulsion against Penicillium digitatum, and nanoemulsion coating effects on the shelf life of postharvest citrus fruits. The results showed that nanoemulsion has uniform particle size along with good centrifugal stability that has significant antifungal effect with MIC (0.125 mg/mL) and MFC (0.25 mg/mL) values. P. digitatum spore germination was significantly inhibited, and mycelial morphology was changed in a dose dependent manner and membrane permeability changed following nanoemulsion treatment. Furthermore, nanoemulsion coating could potentially reduce the citrus fruit decay rate, weight loss rate and respiratory rate. The soluble solids, vitamin C, and titratable acid contents degradation was delayed, while antioxidant enzyme activities were also significantly increased and maintained during postharvest storage. This study revealed that the nanoemulsion had better antifungal effect and great potential in prolonging the storage period of citrus fruits. Highlights: Stable nanoemulsion was prepared from cinnamaldehyde, eugenol and carvacrol. Nanoemulsion as antifungal agent and coating material for Citrus. Nanoemulsion greatly increased the antifungal effect on Penicillium digitatum. Nanoemulsion coating could extend the shelf life of citrus after harvest.